Lost in transition? Complexity in organisational behaviour. The contributions of systems theories - Guido Strunk; Michael Schiffinger; Wolfgang Mayrhofer (Management Revue, 2004)
The article demonstrates the usefulness of concepts and methods from systems theories for Organisational Behaviour (OB). Diagnosing development areas in OB, especially the analysis of whole systems and the degree of operationalisation and formalisation of core constructs and assumptions, the article uses the complexity hypothesis in career research to illustrate the opportunities and limitations of concepts and methods from systems theories. Finally, the consequences of such an approach for OB are discussed.
Keywords: 650; nonlinear systems; synergetics; research methods; career research; Systemtheorie; Verhalten in Organisationen